DIRECTIONALITY: TYPES AND FREQUENCY OF REPAIRS IN SIMULTANEOUS INTERPRETATION - Dailidėnaitė, Alina (Vertimo studijos, 2017)
The article describes an experimental study of self-corrections in simultaneous interpretation (SI) in relation to directionality while making use of previous studies in this field on cognitive processes and strategies in SI. The paper aims to contribute to the literature regarding repair strategies the interpreter resorts to during SI, and examine their possible link to directionality between the language pairs Lithuanian-English and Turkish-English by way of an experimental study. The experiment was carried out with 8 students each working in two directions, from English (B) into Lithuanian (A) or Turkish (A) and the reverse. The material analysed comprises the types and frequency of self-repairs in SI and the reflections on the retrospective verbal protocols provided by the subjects, prompted by listening to the source texts and their interpretations directly after the interpreting task. The results of the study suggest that the types and frequency of repairs differ greatly when interpreting into A and B. The conclusions of the study present some pedagogical implications for training future interpreters.